Metabolism and Development during Conidial Germination in Response to a Carbon-Nitrogen-Rich Synthetic or a Natural Source of Nutrition in Neurospora crassa - Zheng Wang (American Society for Microbiology, 2019)
ABSTRACT Fungal spores germinate and undergo vegetative growth, leading to either asexual or sexual reproductive dispersal. Previous research has indicated that among developmental regulatory genes, expression is conserved across nutritional environments, whereas pathways for carbon and nitrogen metabolism appear highly responsive—perhaps to accommodate differential nutritive processing. To comprehensively investigate conidial germination and the adaptive life history decision-making underlying these two modes of reproduction, we profiled transcription of Neurospora crassa germinating on two media: synthetic Bird medium, designed to promote asexual reproduction; and a natural maple sap medium, on which both asexual reproduction and sexual reproduction manifest. A later start to germination but faster development was observed on synthetic medium. Metabolic genes exhibited altered expression in response to nutrients—at least 34% of the genes in the genome were significantly downregulated during the first two stages of conidial germination on synthetic medium. Knockouts of genes exhibiting differential expression across development altered germination and growth rates, as well as in one case causing abnormal germination. A consensus Bayesian network of these genes indicated especially tight integration of environmental sensing, asexual and sexual development, and nitrogen metabolism on a natural medium, suggesting that in natural environments, a more dynamic and tentative balance of asexual and sexual development may be typical of N. crassa colonies. IMPORTANCE One of the most remarkable successes of life is its ability to flourish in response to temporally and spatially varying environments. Fungi occupy diverse ecosystems, and their sensitivity to these environmental changes often drives major fungal life history decisions, including the major switch from vegetative growth to asexual or sexual reproduction. Spore germination comprises the first and simplest stage of vegetative growth. We examined the dependence of this early life history on the nutritional environment using genome-wide transcriptomics. We demonstrated that for developmental regulatory genes, expression was generally conserved across nutritional environments, whereas metabolic gene expression was highly labile. The level of activation of developmental genes did depend on current nutrient conditions, as did the modularity of metabolic and developmental response network interactions. This knowledge is critical to the development of future technologies that could manipulate fungal growth for medical, agricultural, or industrial purposes.